The Role of Noncoding RNA Pseudouridylation in Nuclear Gene Expression Events - Zhao, Yang; Dunker, William; Yu, Yi-Tao; Karijolich, John (Frontiers in Bioengineering and Biotechnology, 2018)
Pseudouridine is the most abundant internal RNA modification in stable noncoding RNAs (ncRNAs). It can be catalyzed by both RNA-dependent and RNA-independent mechanisms. Pseudouridylation impacts both the biochemical and biophysical properties of RNAs and thus influences RNA-mediated cellular processes. The investigation of nuclear-ncRNA pseudouridylation has demonstrated that it is critical for the proper control of multiple stages of gene expression regulation. Here, we review how nuclear-ncRNA pseudouridylation contributes to transcriptional regulation and pre-mRNA splicing.